If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-1n + -8) + -2(8n + 6) = n + -8n Reorder the terms: -3(-8 + -1n) + -2(8n + 6) = n + -8n (-8 * -3 + -1n * -3) + -2(8n + 6) = n + -8n (24 + 3n) + -2(8n + 6) = n + -8n Reorder the terms: 24 + 3n + -2(6 + 8n) = n + -8n 24 + 3n + (6 * -2 + 8n * -2) = n + -8n 24 + 3n + (-12 + -16n) = n + -8n Reorder the terms: 24 + -12 + 3n + -16n = n + -8n Combine like terms: 24 + -12 = 12 12 + 3n + -16n = n + -8n Combine like terms: 3n + -16n = -13n 12 + -13n = n + -8n Combine like terms: n + -8n = -7n 12 + -13n = -7n Solving 12 + -13n = -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. 12 + -13n + 7n = -7n + 7n Combine like terms: -13n + 7n = -6n 12 + -6n = -7n + 7n Combine like terms: -7n + 7n = 0 12 + -6n = 0 Add '-12' to each side of the equation. 12 + -12 + -6n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -6n = 0 + -12 -6n = 0 + -12 Combine like terms: 0 + -12 = -12 -6n = -12 Divide each side by '-6'. n = 2 Simplifying n = 2
| 12y^3-16y^2+4y=0 | | 18a+21= | | (3x-22)=80+x | | 3x+5-2=11-8 | | 8(5x-3)3.2=y | | -(-93)= | | 2x(9-x)= | | 8(n+8)=-8(-5n+1)+4n | | 27m-7m=40 | | 15x=3y+6 | | 8y-62=-y-8 | | 60x-153=9x | | 0.05(n+10)=0.95 | | 12r+17r= | | ((5x+10)+1)=4x | | 4c-7=37 | | -25-11x=-6x | | -12=9+-7x | | -4(n+3)+3=-3n-3(3-n) | | 9+(3b+8)=(3b+8+9) | | 216x^4-600x^2=0 | | 3x+5x-2=4x-10 | | 2x+3=-11+4x | | 5d+3d+2d-4d=12 | | x^2+26+160=0 | | 4*-9-70=12*-9+2 | | -2+7x=5(-6+7) | | -3(7v+5)+7v=-5+3(v+8) | | 12r+17r=105 | | 2x+2x+3x-2+3x-2=3x-1+3x+3x+1 | | 9-2y=-11+6 | | -6=2n-3n |